A transmutation operator method for solving the inverse quantum scattering problem*Research was supported by CONACYT, Mexico via the projects 222478 and 284470. Research of Vladislav Kravchenko was supported by the Regional mathematical center of the Southern Federal University, Russia. (3rd December 2020) - Kravchenko, Vladislav V; Shishkina, Elina L; Torba, Sergii M
Abstract: The inverse quantum scattering problem for the perturbed Bessel equation is considered. A direct and practical method for solving the problem is proposed. It allows one to reduce the inverse problem to a system of linear algebraic equations, and the potential is recovered from the first component of the solution vector of the system. The approach is based on a special form Fourier–Jacobi series representation for the transmutation operator kernel and the Gelfand–Levitan equation which serves for obtaining the system of linear algebraic equations. The convergence and stability of the method are proved as well as the existence and uniqueness of the solution of the truncated system. Numerical realization of the method is discussed. Results of numerical tests are provided revealing a remarkable accuracy and stability of the method.